DEPARTMENT OF FOREIGN ECONOMIC ACTIVITY BASED ON THE MODEL OF ACCOUNTING POLICY OF EXPORT-IMPORT OPERATIONS - KONONOV, IGOR (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The purpose of the article is to develop practical recommendations for substantiating the sequence of management of foreign economic activity on the basis of the model of accounting policy of export-import operations.It is proposed to define the accounting policy as a set of principles, rules, methods of methods and procedures, the choice of accounting alternatives that ensure the formation and presentation of financial statements and improve the efficiency of export-import operations of trade enterprises. In the order on the accounting policy in terms of coverage of accounting issues of export-import transactions, it is proposed to allocate such sections as general provisions, methods, techniques and organization of accounting. It is proposed to take into account the requirements of the BEPS action plan in Ukraine in the model of accounting policy of foreign economic activity of trade enterprises and to identify objects of accounting policy that will allow choosing an alternative pricing method taking into account the jurisdiction in which the foreign economic activity participant is registered. The organizational sequence of management of foreign economic activity on the basis of the model of accounting policy of export-import operations is developed. It is proved that the choice of an alternative method of pricing taking into account the jurisdiction in which the participant in foreign economic activity is registered or carries out its activities, is a key stage in the management of foreign economic activity of trade. The conditions under which one or another method of transfer pricing is chosen and the peculiarities of application of each of the methods are analyzed. The main characteristics of the method of comparative uncontrolled price, "cost plus", resale price, net profit and profit distribution are given. It is proposed to create a separate internal regulation "Transfer Pricing Policy" as an Annex to the Order on Accounting Policy. The document proposes to separate the sections: regulations for the exchange of information between members of a group of companies involved in foreign trade operations; product description and competition analysis; availability of certificates of conformity; essential terms of contracts, features of pricing and loyalty programs; tax and customs regimes; characteristics of the counterparty (identification of connection, residence, tax status); conditions for recognizing and monitoring transactions as controlled; choice of transfer pricing method; selection of elements of reporting on controlled transactions.
Keywords: accounting policy; foreign economic activity operations; transfer pricing; management of trade enterprises; group of companies; export-import operations